ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN SEBELUM DAN SESUDAH IPO - Subaru, Muhammad Adib; -, Endarwati (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
The purpose of this study is to evaluate the financial performance of PT Archi Indonesia Tbk before and after the Initial Public Offering (IPO). This research analyzes four financial ratios, namely Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Total Asset Turnover (TATO). This study is important because there is a general assumption that an IPO can improve a company's financial performance, but empirical results do not always align with this belief. Therefore, it is necessary to conduct an in-depth examination to determine whether the IPO has a significant impact on the company’s financial performance. PT Archi Indonesia Tbk, which conducted its IPO in 2021, is used as the object of this research. The researcher employs a descriptive quantitative approach by comparing the average values of the financial ratios over three years before and three years after the IPO. The analysis techniques used are the Paired Sample t-Test and the Wilcoxon Signed Rank Test to determine the significance of changes in the ratios before and after the IPO. The conclusion of this study shows a decline in all financial ratios after the IPO; however, there is no statistically significant difference. This indicates that the IPO has not yet had a tangible impact on the short-term financial performance of PT Archi Indonesia Tbk.